Fenología de 100 principales especies vegetales de importancia forestal en relación con las condiciones climáticas a partir de información registrada en el Herbarium Amazonense, Loreto – Perú - Huaranca Acostupa, Richard Javier (2025)
The Peruvian Amazon, a biodiversity hotspot, is facing severe deforestation, highlighting the need for precise conservation strategies. However, detailed information on the phenology of its forest species and their relationship with climate is limited, and herbarium data present biases. This thesis aimed primarily to determine the phenological behavior of 100 key forest species, using 758 fertile specimens from the Herbarium Amazonense. The research sought to record their flowering and fruiting cycles, analyze their geographic distribution, and correlate these patterns with temperature and precipitation. The methodology was quantitative, non-experimental, and descriptive correlational, employing statistical analyses and geospatial tools. The results identified 31 families and 100 species, with Annonaceae, Myristicaceae, and Fabaceae as the most represented. At the community level, flowering was concentrated in the dry season and fruiting in the rainy season. A great diversity of phenological strategies was observed at the species level, including continuous, synchronized, and bimodal patterns, suggesting temporal niche partitioning. Direct correlations with climate were weak at the community level but highly variable at the species level, indicating that multiple factors (such as soil moisture, radiation, and biotic interactions) influence phenology. The geographic distribution of the records showed a strong concentration in Loreto, evidencing sampling biases. In conclusion, this study establishes a fundamental basis for understanding the complex Amazonian phenology, emphasizing the need for differentiated and adaptive conservation and reforestation approaches in the face of climate change.